Are dabbling ducks major players or merely noise in freshwater ecosystems? A European perspective, with references to population limitation and density dependence - Elmberg, Johan (Wildfowl, 2009)
Waterfowl ecologists consider ducks important players in patterns and processes of freshwater ecosystems. Limnologists and fish biologists, on the other hand, historically have â€œa bottom-upâ€ view of the same systems, often regarding waterbirds as â€œbackground noiseâ€ compared to other biotic influences. Evidence for and against these largely opposing views is reviewed, focussing on European dabbling duck studies. In oligo- and mesotrophic wetlands at low breeding density, their role is likely to be overshadowed by biotic interactions between fish, invertebrates and plants. Conversely, many other freshwater systems may be affected by dabbling ducks in various ways, acting as dispersers of invertebrates and plants, as predators, and as eutrophicators. It is concluded that dabbling ducks affect freshwater systems more profoundly than has hitherto been acknowledged. In their turn, freshwater ecosystems affect the ducksâ€™ population ecology. In a less comprehensive treatment, the evidence for the major paradigms addressing population limitation in dabbling ducks is discussed briefly from a European perspective. It is concluded that top-down (predation) as well as bottom-up (food limitation) processes may both affect population size, but evidence for either is correlative, necessitating more experimental studies based on explicit predictions from pattern-oriented studies. In a discussion of the prospects for adopting a more adaptive management approach for European dabbling ducks, it is argued that a lack of information about annual variation in recruitment and harvest rates are major obstacles to understanding population change and for adopting a more adaptive management. A compilation of European studies about density dependence in Mallard Anas platyrhynchos indicates that population regulation may be a common phenomenon in this species, with possible important ramifications for research as well as management programmes.